Openness to Interorganizational Cooperation: A Study of Hospital Administrators - Schermerhorn, John R. (Academy of Management Journal, 1976)
Survey data support several correlates of hospital administrator openness to programs of interhospital cooperation. The data fail to support the hypothesis that openness to cooperation is subject to distress motivation; rather, there is indication such openness is more likely when the administrator considers the hospital a high performer. Implications of these findings are discussed.